PENGARUH KEPEMIMPINAN DAN KETERLIBATAN PEKERJA TERHADAP KINERJA PELAYANAN (Studi Kasus pada Kantor UPT Puskesmas DTP Kecamatan Ciruas Kabupaten Serang) - Mukhsin, Moh. (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2017)
The objective of these researches are to know how implementation of Leadership and Workers Involvement Influence on Service Performance at UPTD office sub-district Puskesmas DTP Ciruas Serang District. This research used quantitative method by using descriptive research and causal research. Data from the 3 variables were analyzed by using SPSS 16.00 program. The number of samples used in this study were 52 respondents. Based on the data analysis it can be concluded that there is no leadership program and employee involvement, the value of service performance of 2.162 units. The leadership regression coefficient (0.441) means that if the leadership program is increased by 1 unit, then the service performance will increase by 0.441 units. Leadership regression coefficient of (0.538) means that if the leadership condition is increased by 1 unit then the service performance will increase by 0.538 units. Result of hypothesis test where Fcount> Ftable (68,762> 3,194). With a real level of 5% which means Ho is rejected and Ha accepted. This indicates that the leadership and the involvement of workers significantly influence the service performance at UPTD office sub-district Puskesmas DTP Ciruas Serang District.